Implementing a nurse-delivered cognitive behavioural therapy intervention to reduce the impact of hot flushes/night sweats in women with breast cancer: a qualitative process evaluation of the MENOS4 trial - Cherish Boxall; Deborah Fenlon; Carl May; Jacqui Nuttall; Myra S. Hunter (BMC Nursing, 2023)
Abstract Background Hot flushes and night sweats are life-altering symptoms experienced by many women after breast cancer treatment. A randomised controlled trial (RCT) was conducted to explore the effectiveness of breast care nurse (BCN)-led group cognitive behavioural therapy (CBT). This paper reported findings from a qualitative process evaluation to optimise the CBT intervention and explore the determinants of implementation into routine practice. Methods Qualitative process evaluation occurred in parallel with the RCT to explore patient and healthcare staff experiences and perspectives using semi-structured interviews pre-and post-intervention. Normalisation Process Theory (NPT) informed data collection, analysis, and reporting of findings. The analysis involved inductive thematic analysis, NPT coding manual and subsequent mapping onto NPT constructs. Results BCNs (n = 10), managers (n = 2), surgeons (n = 3) and trial participants (n = 8) across six recruiting sites took part. All stakeholders believed group CBT met a need for non-medical hot flushes/night sweats treatment, however, had little exposure or understanding of CBT before MENOS4. BCNs believed the work fitted with their identity and felt confident in delivering the sessions. Despite little understanding, patients enrolled onto group CBT because the BCNs were trusted to have the knowledge and understanding to support their needs and despite initial scepticism, reported great benefit from group-based participation. Both managers and surgeons were keen for BCNs to take responsibility for all aspects of CBT delivery, but there were some tensions with existing clinical commitments and organisational priorities. Conclusions Both healthcare staff and patient participants believe BCN-led group CBT is a beneficial service but barriers to long-term implementation into routine care suggest there needs to be multi-level organisational support. Trial registration NCT02623374 – Last updated 07/12/2015 on ClinicalTrials.gov PRS.